2019
DOI: 10.1021/acs.orglett.9b02812
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Activation of C–I Bonds and Perfluoroalkylation of Alkenes with Visible Light Using Phosphine Catalysts

Abstract: An efficient metal-free, photomediated iodo perfluoroalkylation under mild conditions was developed. Using catalytic amounts (10 mol %) of phosphines and blue light irradiation, various olefins are transformed into the corresponding addition products within short reaction times. For this purpose, a modular and convenient 3D printed photoreactor was constructed, which is presented as an open source model. The reaction presumably proceeds upon generation of perfluoroalkyl radicals, which are formed by catalyst-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 69 publications
2
56
0
Order By: Relevance
“…The results of the present computational chemistry study support the mechanism of a phosphine-assisted light-induced homolytic C-I bond cleavage, proposed earlier by some of us [40] on the basis of experimental observations. In addition, they provide an explanation for the fact that t Bu 3 P is a much better photocatalyst in the blue-light regime than n Bu 3 P. While the origin of the S 1 ←S 0 absorption band should be energetically accessible to blue-light radiation in both butylphosphine-IC 4 F 9 adducts, the larger coordinate displacements of the ground and excited singlet potential energy wells in n Bu 3 P-IC 4 F 9 reduce the overlaps of the vibrational wave functions and thus the absorption probability compared to t Bu 3 P-IC 4 F 9 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the present computational chemistry study support the mechanism of a phosphine-assisted light-induced homolytic C-I bond cleavage, proposed earlier by some of us [40] on the basis of experimental observations. In addition, they provide an explanation for the fact that t Bu 3 P is a much better photocatalyst in the blue-light regime than n Bu 3 P. While the origin of the S 1 ←S 0 absorption band should be energetically accessible to blue-light radiation in both butylphosphine-IC 4 F 9 adducts, the larger coordinate displacements of the ground and excited singlet potential energy wells in n Bu 3 P-IC 4 F 9 reduce the overlaps of the vibrational wave functions and thus the absorption probability compared to t Bu 3 P-IC 4 F 9 .…”
Section: Discussionsupporting
confidence: 90%
“…In our studies addressing the Lewis-base-mediated iodoperfluoroalkylation of simple alkenes [40,42,43] we found that catalytic amounts of phosphines and phosphites effectively catalyze this process with complete regioselectivity upon irradiation with visible light (461 nm) (Scheme 1). Mechanistic investigations involving 19 F-NMR analysis suggested the intermediate formation of an EDA complex F(CF 2 ) n -I • • • PR 3 by halogen bond formation to the phosphorus atom [44,45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We started by visible light irradiation of a mixture of 1-octene and C 4 F 9 I with or without added t Bu 3 P under similar conditions as those of the FLP-catalyzed reaction. 20 Surprisingly, we obtained a yield of 89% after a reaction time of 1 hour in the presence of t Bu 3 P (10 mol%). Without the phosphine, no conversion was detected after 72 hours and only 32% after 49 days.…”
Section: Scheme 5 Flp-catalyzed Iodoperfluoroalkylation Of Alkenes Inmentioning
confidence: 84%
“…One of the major improvements has been made via photo-excited catalyst such as Ru/Ir complexes and organic dyes [21,33]. Very recently, non-covalent interaction initiated fluoroalkylation reaction has emerged as an attractive strategy [37][38][39][40][41][42][43][44][45][46][47]. Inspired by our previous studies in this field [48][49][50][51], we envision that if the solvent can serve as an electron donor compound, the reactions would be simpler.…”
Section: Introductionmentioning
confidence: 99%